Health and justice related substance misuse in Wales: creating an e-cohort of intergenerational households - Evans, Hywel T; Farr, Ian; Bailey, Grace; Davies, Gareth; Dixon, Josh; Fallick, Sam; Maimaris, Joanne; Ohaeri, Columbus; Oluwasuji, Olabambo; Phillips, Ryan; Skermer, Matthew; James, Delyth; et al. (International Journal of Population Data Science, 2025)
Objectives Household substance misuse (SM) is associated with child deprivation and worse physical and mental health. This study utilised linked healthcare, justice, and social care data in Wales for the first time, to create a reusable cohort of households that experience substance misuse (SMHH). Methods Using the Secure Anonymised Information Linkage (SAIL) Databank, a population-scale retrospective electronic cohort (e-cohort) study identified SM-related health and criminal justice events during 2011–2019 for adults and children in SMHH, which were compared with the rest of the population using period prevalence ratios (PR) and 95% confidence intervals (CI). Other variables included demographics, children’s social care, healthcare, and SM-related criminal court cases. Results There were 776,366 children and 1,032,088 adults, where 83,558 children (11%) lived in SMHH, and 48,398 (5%) of adults who lived with a child had a SM event. Children in SMHH were themselves 1.3 times more likely to be referred to SM treatment (PR = 2.33, CI: 2.23–2.43), and 42% more likely to have a SM-related criminal case (PR = 1.42, CI: 1.30–1.55) during the period. Notably, SMHH children were 3.0 times more likely to receive care and support (PR = 4.00, CI: 3.92–4.08), and 78.1% (PR = 1.78, CI: 1.71–1.86) more likely to self-harm. Conclusion SMHH children experience significant disparities, including higher deprivation, adverse birth outcomes, mental health issues, social care involvement, and SM-related criminal justice prosecutions. Evidence-based interventions and policy are needed to support adults and children in SMHH to mitigate the intergenerational impact.